Exploration of the current status and trends of pancreatic cancer immune cells in the past 30 years: a bibliometric analysis - Yang Hu; Simeng Lei; Zihan Zhang; Kexin Wang; Zhili Ji (Discover Oncology)
Abstract Objective Immune cells are pivotal in progressing and treating pancreatic cancer. Over the past three decades, the complex interactions between pancreatic cancer and immune cells have garnered much attention, as evidenced by the increasing number of publications in this domain. This bibliometric study maps the global research landscape of pancreatic cancer immune cell interactions, emphasizing evolving trends, collaborative networks, and therapeutic innovation. Method Using VOSviewer and CiteSpace, we analyzed 2658 articles from the Web of Science Core Collection (2000–2024) to evaluate publication trends, collaborative networks, keyword dynamics, and highly cited works. Results Annual publications surged from 4 (2000) to 453 (2024), with China (44.9%) and the U.S. (33.6%) dominating output. Key institutions included Fudan University (102 articles) and Zhejiang University (88 articles). Keyword evolution revealed three phases: antitumor mechanisms, clinical translation of checkpoint inhibitors, and recent emphasis on stromal-immune crosstalk. High-impact works by Brahmer (N Engl J Med 366:2455–2465, 2012) and Marabelle (J Clin Oncol 38:1–10, 2020) underscored immunotherapy milestones. Conclusion This bibliometric analysis highlights the dynamic nature of pancreatic cancer immune cell research, emphasizing the growing global interest and investment in this field. The findings underscore the need for ongoing monitoring of research trends to inform and propel innovative therapeutic strategies, ultimately improving patient outcomes.